Karakteristik Pengguna Media Sosial - Diah Isnaini Asiati; Septadiyanto Septadiyanto (MBIA, 2018)
The development of technology has resulted in the development of communication media through social media. The use of this media varies in terms of its demographic characteristics, whereas the benefits of this media for each group are different. Therefore, to maximize the benefits of technological advancements, it is important to study the accuracy of the group of users. This study aims to determine the distinguishing characteristics of social media users. The study used a number of 93 samples taken in clusters. The results showed that there were no differences in the characteristics of social media users based on gender and religion. The characteristics of social media users are especially those who are students. This group has the highest frequency of use for entertainment and communication purposes.